SOSIALISASI PENGOLAHAN PAKAN DAN KOTORAN TERNAK DENGAN TEKNOLOGI BIOFERMENTASI - P.A. Astawa G. Mahardika K. Budaarsa dan K. M. Budiasa (Buletin Udayana Mengabdi, 2013)
Livestock group of Kaliakah Village, Jembrana Regency is one of the groups which are raising bali cattle in theirdaily life. Their members are mostly farmers having productive lands. They feed their cattle with greens obtainedby trimming the grass, however they sometimes feed them with rice-straws although somehow they do not proceedmaximally them. Referring to the above conditions, we conducted socialization and demonstration about how toproceed rice-straws and cattle’s manure by bio-fermentation technology. Rice-straws were proceeded by biochastfermentor and manure with Rumino Bacillus. Biochast, in one hand consists of Ruminococcus, Bakteroides,Lactobacillus and Streptococcus. On the other hand Rumino Bacillus consists of Rummino Coccus and Bacillus.Sugar is a fermentation media. Rice-straws and manure processes were completely done from 1 until 2 weeks.The proceeded rice-straws can be stored until 3 to 4 months, however manures can be anytime